2005
DOI: 10.1001/archpsyc.62.3.263
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Complexin Proteins and Cognitive Dysfunction in Schizophrenia

Abstract: The pathology of hippocampal complexin proteins might play an important role in schizophrenia, especially concerning cognitive disturbances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
70
0
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(81 citation statements)
references
References 49 publications
9
70
0
2
Order By: Relevance
“…Evidence for synaptic dysfunction in psychiatric disorders Expression changes in many synaptic-associated proteins such as synaptophysin, complexin I and II, synaptosomal-associated protein (SNAP)-25 and syntaxin (for example Eastwood et al, 43 Sawada et al, 44 Owen et al 45 and Frankle et al 46 ) have been found in schizophrenia. In addition, these protein changes are in keeping with synaptic-associated roles for many of the recently described candidate genes for schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence for synaptic dysfunction in psychiatric disorders Expression changes in many synaptic-associated proteins such as synaptophysin, complexin I and II, synaptosomal-associated protein (SNAP)-25 and syntaxin (for example Eastwood et al, 43 Sawada et al, 44 Owen et al 45 and Frankle et al 46 ) have been found in schizophrenia. In addition, these protein changes are in keeping with synaptic-associated roles for many of the recently described candidate genes for schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…23 Indeed, synaptic disturbance in schizophrenia is well described, involving both the pre-and postsynaptic machinery, and is considered a characteristic feature of this complex disorder. [24][25][26][27] However, mRNA may not be the most reliable method to use in order to gain insight into the underlying pathophysiology of schizophrenia, where abnormalities in gene function may or may not affect downstream protein expression. 28,29 To approach this issue, proteomic techniques have been used, on a complementary basis, to investigate the underlying molecular abnormalities in the cortex in schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…CME is important for both presynaptic and postsynaptic functions and both functions have been implicated in schizophrenia [73][74][75] . In presynaptic axon terminals, CME is required for the retrieval of synaptic vesicle proteins following neurotransmitter release, and for the recycling of vesicles back to the reserve pool 7 .…”
Section: Altered Cme May Contribute To Synaptic Pathologymentioning
confidence: 99%
“…Possibly a hypofunction of the glutamatergic NMDA receptor acting on long-term potentiation disturbs synaptic plasticity 70 . On the molecular level there is strong support for decreased synaptic plasticity, mainly affecting the expression of presynaptic vesicle proteins including the synaptosome-associated protein 25 (SNAP-25) and syntaxin forming the soluble N-ethylmaleimide-sensitive factor attachment protein receptor (SNARE) complex [71][72][73][74][75][76][77][78][79] . The trimeric SNARE complex is involved in membrane fusion and exocytosis of neurotransmitters.…”
Section: Schizophrenia As a Disorder Of Disturbed Synaptic Plasticitymentioning
confidence: 99%
“…A more consistent finding within the hippocampus is abnormal synaptic connectivity, as shown by decreased expression of the presynaptic proteins synapsin, synaptophysin and SNAP-25 73 . In addition, disturbances of complexins in the hippocampus were associated with the severity of ante-mortem cognitive impairment 78 . Further insights in disturbed synaptic plasticity provided a microarray study of the superior temporal cortex, showing that decreased expression of immune-related genes may affect synaptic strength and transmission 44 .…”
Section: Schizophrenia As a Disorder Of Disturbed Synaptic Plasticitymentioning
confidence: 99%